Максимальна урожайність або прибутковість: пріоритети вибору в умовах інноваційного розвитку - Олійник, Олександр Васильович; Макогон, Віталій Вікторович; Брік, Світлана Володимирівна (Національний науковий центр "Інститут аграрної економіки", 2019)
The purpose of the article is to investigate the influence of innovative processes in agricultural enterprises on the formation of financial results from the production and sale of major types of products. Research methods. The research was based on: the dialectical method of cognition; the monographic method (for the analysis of approaches to application of innovations); the empirical method (for assessing the development of domestic grain and oilseed industries); the graphic method (for highlighting the trends in efficiency of the wheat grain production); the correlation and regression analysis (for establishing the dependencies between productive and cost-based indicators of the wheat grain production and determination of an optimal level of costs); the grouping method (for assessing management priorities in the planning of the grain production intensity); abstract and logical methods (for theoretical generalizations and formulation of conclusions). Research results. Introduction of innovations in the agrarian production contributed to the increase of crop page, but was accompanied by a loss of 13-18% of the potential profit. This requires an analysis of financial performance of implemented innovative technologies. At the same time, it is important to consider both the technological evaluation of payback and increase of yield, as well as the economic one from the point of view of a margin of each technological innovation application. Elements of the scientific novelty. The theoretical approaches to determining an optimal level of intensive production were further developed. In particular, the need to consider a profit maximization criterion when substantiating the introduction of technological innovations in the agricultural production was proved. Practical significance. Along with positive effects of the introduction of innovations in the agrarian sector, the latter leads to a lack of potential profit, which actualizes the need to assess financial effectiveness of implemented technologies. Tabl.: 3. Figs.: 1. Refs.: 20
Maximum yield or profitability: priorities for choice in conditions of innovative development
Keywords: інноваційний розвиток; витрати; оптимум витрат; урожайність; прибуток; інтенсивність виробництва; innovative development; costs; optimum of costs; yield; profit; production intensity